2012
DOI: 10.1186/1472-6882-12-109
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to melanin and to tyrosinase in melanoma patients, and in people with vitiligo

Abstract: BackgroundThe aim of this study was to determine the presence and the intensity of humoral immunity to melanoma-associated antigens: tyrosinase and melanin, in patients with melanoma, in persons with vitiligo and in control healthy people.MethodsThe study involved 63 patients with melanoma and 19 persons with vitiligo. Control group consisted up to 41 healthy volunteers. Mushroom tyrosinase and synthetic melanin were used as the antigens.ResultsELISA test showed significantly (p < 0.0000004 and p < 0.04) lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Not much is known about melanoma-specific antibodies and their relation to clinical outcome from literature. 22-24 The majority of immunomonitoring in immunotherapy studies focus on T-cell responses, in particular specific CD8+ T-cell responses using tetramer technology or activation assays. We demonstrated that patients with melanoma-associated vitiligo have antibodies against gp100, tyrosinase and MART-1 in their serum while MART-1 antibodies were undetectable in vitiligo patients, 4 indicating their potential role in the melanoma-associated vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Not much is known about melanoma-specific antibodies and their relation to clinical outcome from literature. 22-24 The majority of immunomonitoring in immunotherapy studies focus on T-cell responses, in particular specific CD8+ T-cell responses using tetramer technology or activation assays. We demonstrated that patients with melanoma-associated vitiligo have antibodies against gp100, tyrosinase and MART-1 in their serum while MART-1 antibodies were undetectable in vitiligo patients, 4 indicating their potential role in the melanoma-associated vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…tyrosinase) are highly immunogenic. 34,35 Various kinds of melanins revealed immunomodulatory activity by regulating cytokine production by T-lymphocytes and monocytes, as well as fibroblasts and endothelial cells. 34 It was even reported that the edible mushrooms, as they are a rich source of melanin and tyrosinase, may induce immunity to these antigens in humans.…”
Section: Discussionmentioning
confidence: 99%
“…34 It was even reported that the edible mushrooms, as they are a rich source of melanin and tyrosinase, may induce immunity to these antigens in humans. 35 The possible role of melanin-related antigens in human autoimmunity remains, however, a field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of melanins revealed immunomodulatory activity by regulating cytokine production by T-lymphocytes and monocytes, as well as fibroblasts and endothelial cells [15]. It was even reported that the edible mushrooms, as they are a rich source of melanin and tyrosinase, may induce immunity to these antigens in humans [16].…”
Section: Discussionmentioning
confidence: 99%
“…tyrosinase) are highly immunogenic [16]. Various kinds of melanins revealed immunomodulatory activity by regulating cytokine production by T-lymphocytes and monocytes, as well as fibroblasts and endothelial cells [15].…”
Section: Discussionmentioning
confidence: 99%